2016
DOI: 10.1155/2016/3027363
|View full text |Cite
|
Sign up to set email alerts
|

Placental Growth Factor, Soluble fms-Like Tyrosine Kinase 1, Soluble Endoglin, IL-6, and IL-16 as Biomarkers in Preeclampsia

Abstract: Preeclampsia (PE), an important cause of maternal and perinatal morbidity and mortality worldwide, is a pregnancy-related disease characterized by hypertension and proteinuria after 20 weeks of gestation. The aim of our study was to find a practical panel of biomarkers useful in early diagnosis of PE. This study was carried out at the Obstetrics and Gynecology Department in Tîrgu Mureș University Hospital, Romania, between January 2014 and July 2015 and included 68 pregnant women (47 preeclamptic women and 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…This increase in IL16 in pregnant women was found to be associated with pre-eclampsia and preterm birth [22][23][24]. Kuzmicki et al have shown that the balance between circulating pro-and anti-inflammatory cytokines is impaired in patients with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in IL16 in pregnant women was found to be associated with pre-eclampsia and preterm birth [22][23][24]. Kuzmicki et al have shown that the balance between circulating pro-and anti-inflammatory cytokines is impaired in patients with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…A newer study confirmed the elevated levels of IL‐6 both in early‐ and late‐onset PE, while Taylor et al did not observe a significant increase in the first and second trimester. Moreover, Rădulescu et al showed that although second‐trimester IL‐6 was significantly elevated, its diagnostic efficacy was not adequate (AUC: 0.568). Finally, it is notable that in a recent study, treatment with MgSO 4 and nifedipine lead to a considerable decrease in IL‐6 levels (from 24.49 pg/mL [4.71‐237] to 13.23 pg/mL [1.78‐196]).…”
Section: Resultsmentioning
confidence: 99%
“…The findings of El‐Baradie et al support the aforementioned IL‐16 increase and add their calculated predictive value of IL‐16 for PE development (sensitivity = 88.89%, specificity = 95.92%). Following a similar methodology, Rădulescu et al presented a diagnostic accuracy analysis for IL‐16: The AUC of the ROC curve was 0.682, thus qualifying the marker as a relative “good predictor” for PE. Therefore, there is evidence that PE is associated with significantly increased levels of circulating IL‐16.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has also been reported that the hypoxia-inducible factor-1 alpha (HIF-1α), which appears to be a master regulator of the cellular response to hypoxia [50], regulates PrPc expression in order to protect against neuron cell damage [51]. In correlation with this, a variety of studies have shown that women with PE are characterized by persistently elevated placental HIF-1α levels that promote enhanced transcription of genes encoding the soluble antiangiogenic protein fmslike tyrosine kinase-1 (sFlt-1), the soluble antiagiogenic factor endoglin (sEngs) and endothelin-1 (ET-1), a powerful vasoconstrictor known to contribute to this pregnancy pathology [52][53][54][55][56]. Moreover, Donadio et al [57] and Alfaidy et al [58] reported that PrPc is highly expressed in the human placenta, especially in CT and ST, and Hwang et al [59] found that the immunohistochemical expression of PrPc was increased in CT and ST of PE placentas versus those from the controls.…”
Section: Normal Cellular Prion Protein Form In Placentamentioning
confidence: 99%